2005
DOI: 10.1017/s002211200400326x
|View full text |Cite
|
Sign up to set email alerts
|

On the role of non-equipartition in the dynamics of rapidly flowing granular mixtures

Abstract: For rapidly flowing granular mixtures, existing kinetic-theory descriptions based on an assumed form of the velocity distribution function typically contain one of two simplifying assumptions: a Maxwellian velocity distribution or an equipartition of energy. In the current work, the influence of non-equipartition effects is explored in the context of two flow types: flow in which species segregation does not occur (namely, simple shear flow) and a segregating flow. For the former case, a comparison between exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
80
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 29 publications
9
80
0
Order By: Relevance
“…Nevertheless, the relationship between this kind of driving and actual experiments is uncertain. The non-equipartition has also been confirmed by MD simulations of simple shear flows [5] and of vibrated granular gases (in absence of gravity) [6].…”
Section: Introductionmentioning
confidence: 54%
“…Nevertheless, the relationship between this kind of driving and actual experiments is uncertain. The non-equipartition has also been confirmed by MD simulations of simple shear flows [5] and of vibrated granular gases (in absence of gravity) [6].…”
Section: Introductionmentioning
confidence: 54%
“…These studies have identified several driving mechanisms for segregation, pattern formation, and mixing of bidisperse particles. In the dilute, energetic flow regime, where particles interact mainly through binary collisions, the gradient of granular temperature alone can drive size segregation, which is successfully modeled by kinetic theory (Jenkins & Mancini 1989;Hsiau & Hunt 1996;Khakhar et al 1999;Arnarson & Willits 1998;Galvin et al 2005;Yoon & Jenkins 2006). In contrast, in the dense granular flow regime, particle geometry appears to be the primary driving mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In sheared dilute energetic granular mixtures all particles accumulate in the regions of low shear rateγ corresponding to regions of low T and high f , and larger particles do so more efficiently (e.g., [8][9][10][11]) leaving the latter segregated at the regions of lowestγ and T , highest f . This has been successfully modeled using kinetic theory [8,[11][12][13][14] for sufficiently sparse flows. For moderate solids fractions, kinetic theory has been shown to overpredict segregation trends, though still qualitatively reproduce the outcome [10].…”
mentioning
confidence: 99%
“…[8,11]). All particles move to regions of low-T , low-γ, high f in the center of chute, though large particles do so more efficiently [See Fig.…”
mentioning
confidence: 99%